Measurement of the permanent electric dipole moment of the 129Xe atom - Allmendinger, Fabian; Engin, Ilhan; Heil, Werner; Karpuk, S.; Krause, H.-J.; Niederländer, Benjamin; Offenhäusser, A.; Repetto, Maricel Teresa; Schmidt, Ulrich; Zimmer, Stefan (Physical review, 2019)
We report on a measurement of the CP-violating permanent electric dipole moment (EDM) of the neutral 129Xe atom. Our experimental approach is based on the detection of the free precession of co-located nuclear spin-polarized 3He and 129Xe samples. The EDM measurement sensitivity benefits strongly from long spin coherence times of several hours achieved in diluted gases and homogeneous weak magnetic fields of about 400 nT. A finite EDM is indicated by a change in the precession frequency, as an electric field is periodically reversed with respect to the magnetic guiding field. Our result (−4.7±6.4)×10−28ecm, is consistent with zero and is used to place a new upper limit on the 129Xe EDM: ∣∣dXe|<1.5×10−27ecm (95% C.L.). We also discuss the implications of this result for various CP-violating observables as they relate to theories of physics beyond the standard model.
Die Zahl 129 im Titel ist hochgestellt
Gesehen am 15.06.2020